Application and Validation of an Advanced Gastrointestinal In Vitro Model for the Evaluation of Drug Product Performance in Pharmaceutical Development. Issue 11 (15th September 2014) - Barker, Richard; Abrahamsson, Bertil; Kruusmägi, Martin
<x xml:space="preserve">Abstract</x> Methods to understand and predict the oral bioavailability of drug products are a prioritized research area within the pharmaceutical industry. Models to predict oral bioavailability have the potential to reduce risk, time, and cost in development as well as decrease the need for animal studies. The TNO intestinal model (TIM‐1) is an advanced dissolution model deployed by AstraZeneca since 2008. This article presents a systematic evaluation of TIM‐1 against in vivo data. The relative performance of compounds and formulations tested in TIM‐1 and in vivo was compared both by a qualitative analysis and a linear regression analysis of relative exposure measures between test and reference formulations in TIM‐1 and in vivo. The TIM‐1 correctly predicted in vivo rank order in 84% and 79% of cases for AUC and Cmax, respectively, when using the 3‐h time point. There was only one case for Cmax in which TIM‐1 did not predict an in vivo difference. The correlation coefficient (R2) between relative (test vs. reference formulations) fraction available in TIM‐1 after 3 h and AUC was 0.78. Thus, this study suggests that the TIM‐1 system can be used to assess the risk for significant differences in exposure between formulations and compound modifications. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3704–3712, 2014